Extranodal involvement of diffuse large B-cell lymphoma in the head and neck: An indicator of good prognosis. Issue 1 (February 2019) - Lee, Doh Young; Kang, Karam; Jung, Hwaejoon; Park, Young Min; Cho, Jae-Gu; Baek, Seung-Kuk; Kwon, Soon-Young; Jung, Kwang-Yoon; Woo, Jeong-Soo
Abstract: Objective: In this study, we analyzed clinicopathological characteristics and survival outcomes according to extranodal involvement of diffuse large B-cell lymphoma (DLBCL) in the head and neck. Methods: A retrospective analysis was conducted on 110 patients from 2004 to 2014 with CD20-positive DLBCL involving the head and neck area. Patients were categorized into two groups, extranodal and nodal, according to involvement of extranodal sites in the head and neck. Outcome measurements for the groups included clinical response to treatment and recurrence rates. Results: Palatine tonsils were the most frequently involved extranodal site in the head and neck (29.1%). Among clinicopathological parameters, proportion of patients with lactate dehydrogenase over 350 IU/L (p = 0.033), cell of origin (p < 0.001), and treatment outcomes (p = 0.007) were significantly different between the two groups. Among cell origin markers CD10, Bcl6, and MUM1, MUM1 was significantly correlated with extranodal involvement (p = 0.029). Recurrence rates were similar between groups, while disease-specific survival was significantly higher in the extranodal group (p = 0.011). Disease-specific survival of the extranodal group was also higher than the nodal group with extranodal involvement of other body sites (p = 0.010). Among patients with negative expression of CD10 (p = 0.015), Bcl6 (p = 0.018), and MUM1 (p = 0.005), survival was longer in the extranodal than the nodal group. Conclusions: DLBCL patients with extranodal involvement of the head and neck may have longer survival outcomes than patients with solely nodal involvement. Increased survival may be more prominent in patients with negative expression of CD10, Bcl6, and MUM1.